2016
DOI: 10.3390/catal6110170
|View full text |Cite
|
Sign up to set email alerts
|

An Alumina-Supported Ni-La-Based Catalyst for Producing Synthetic Natural Gas

Abstract: LaNi 5 , known for its hydrogen storage capability, was adapted to the form of a metal oxide-supported (γ-Al 2 O 3 ) catalyst and its performance for the Sabatier reaction assessed. The 20 wt % La-Ni/γ-Al 2 O 3 particles were prepared via solution combustion synthesis (SCS) and exhibited good catalytic activity, achieving a CO 2 conversion of 75% with a high CH 4 selectivity (98%) at 1 atm and 300 • C. Characteristics of the La-Ni/γ-Al 2 O 3 catalyst were identified at various stages of the catalytic process (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…The selectivity of catalysts is slightly changed after introduction of cerium. The observed changes of the activity of promoted catalysts are consistent with recently published data[32][33][34][35][36]. An increased activity of Ce and La promoted nickel catalysts has been often attributed…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The selectivity of catalysts is slightly changed after introduction of cerium. The observed changes of the activity of promoted catalysts are consistent with recently published data[32][33][34][35][36]. An increased activity of Ce and La promoted nickel catalysts has been often attributed…”
supporting
confidence: 91%
“…Such discrepancy may result from limited accessibility of surface sites and partial coverage of nickel crystallites by the support. in the literature to the improved nickel dispersion and changes of the acid-base properties of catalysts [32][33][34][35][36]. Figure 3 shows the results of durability studies of catalysts in CO 2 methantion reaction performed at 475 °C.…”
Section: Properties Of Catalysts Determined Prior To the Co 2 Methanamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rivero-Mendoza et al reported La-Ni/γ-Al 2 O 3 catalytic activity relative to the Sabatier reaction [112], where catalytic studies coupled with in situ DRIFTS analyses provide insights on the CO 2 methanation mechanism. The activation process of the catalyst promotes formation of oxidized Ni particles (Ni 2+ ) decorated with LaO x moieties.…”
Section: Alumina-supported Nickelmentioning
confidence: 99%
“…Methane (CH 4 ), the main constituent of natural gas plays an increasingly important role in meeting future global energy demands [1]. It is widely used in various applications such as electrical power generation and other heating applications.…”
Section: Introductionmentioning
confidence: 99%